Analysis of Nursing Home Residents' Identity Completeness Classification Using the Decision Tree Algorithm - Muhammad Indra; Darmeli Nasution (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study evaluates the effectiveness of the Decision Tree algorithm in classifying the completeness of nursing home residents' identities based on age. The data used includes identity information from 333 residents, encompassing both Family Cards and Identity Cards (KTP). By applying the Decision Tree C4.5 algorithm, the data is classified into the categories of Incomplete, Sufficiently Complete, and Complete. The analysis results indicate that older residents tend to have less complete identities compared to younger residents. These findings highlight the effectiveness of the Decision Tree algorithm in identifying patterns within identity data, facilitating service planning and administrative management in the nursing home, and ensuring regulatory compliance. This research provides a foundation for improving identity management systems and can be used to optimize administration and protection in nursing homes.